Characteristics of headache during and/or after coronary intervention: A prospective observational study. (May 2022) - Lu, Chenglong; Zhang, Leyi; Liu, Cuixiang; Wang, Zhifeng; Zhang, Ran; Wang, Lin; Yang, Ying; Meng, Fanchao; Yu, Shengyuan; Liu, Ruozhuo
Introduction: Headache during and/or after coronary intervention is common but has received little attention from cardiologists and neurologists. The purpose of this study was to investigate the incidence, risk factors, and possible mechanism of coronary intervention-related headache. Methods: Using a prospective observational design, we identified consecutive patients with coronary intervention from May 2020 to August 2020. Patients were followed up with questionnaires immediately after coronary intervention and 24 h, 72 h, 1 week and 2 weeks after the intervention. Results: In total, 94 patients were enrolled, and 71 patients ultimately completed the 2-week follow-up. Among 71 patients, headache developed during and/or after coronary intervention in 18 (25.4%) patients. Two different types of headache related to coronary intervention were observed: One during and another after coronary intervention. Headache characteristics are described in detail. A history of previous headache was an independent risk factor for coronary intervention-related headache ( p < 0.01). Conclusions: Coronary intervention-related headache has an incidence of 25.4%, and previous headache history was an independent risk factor. Moreover, considering that there are no relevant diagnostic criteria, it is suggested that the definition of coronary intervention-related headache should be established in the International Classification of Headache Disorders.